Mean Platelet Volume: An Early Predictor of Diabetic Vascular Complications - Nikita James (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
This chapter aims to determine mean platelet volume (MPV) and platelet count (PC) in diabetics (type2) and non-diabetics and to determine correlation of MPV and platelet count with fasting blood sugar. Increased MPV is emerging as an independent risk factor for thromboembolism, stroke and myocardial infarction. The majority of Diabetes Mellitus deaths are caused by micro- and macro vascular complications of the disease. Larger platelets with larger mean platelet volume are more prone to thrombosis. Over the course of three months, this prospective investigation included 100 participants with type II diabetes and 50 non-diabetic controls. The results showed that diabetics had a significant rise in MPV value. The MPV test, which is simple and affordable, can be used as a useful tool to monitor patients for thrombogenicity, particularly in those with altered blood glucose metabolism.